2015
DOI: 10.1016/j.cell.2015.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Type VI Secretion System Contractile Sheath

Abstract: Summary Bacteria use rapid contraction of a long sheath of the Type VI secretion system (T6SS) to deliver effectors into a target cell. Here we present an atomic resolution structure of a native contracted Vibrio cholerae sheath determined by cryo-electron microscopy. The sheath subunits, composed of tightly interacting proteins VipA and VipB, assemble into a six-start helix. The helix is stabilized by a core domain assembled from four β-strands donated by one VipA and two VipB molecules. The fold of inner and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
284
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(293 citation statements)
references
References 61 publications
9
284
0
Order By: Relevance
“…We isolated the VipA‐N3 sheath variant (3‐amino acid insertion into the N‐terminal VipA linker, tagged with msfGFP) from cells and purified it by ultracentrifugation as described previously (Kudryashev et al , 2015). Negative stain electron microscopy showed sheath assemblies of various lengths in apparently extended conformations (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We isolated the VipA‐N3 sheath variant (3‐amino acid insertion into the N‐terminal VipA linker, tagged with msfGFP) from cells and purified it by ultracentrifugation as described previously (Kudryashev et al , 2015). Negative stain electron microscopy showed sheath assemblies of various lengths in apparently extended conformations (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…However, the subunits of the non‐contractile VipA‐N3 mutant sheath are connected to the previous sheath ring only through VipB linker and the elongated VipA linker connects to a neighboring subunit on the same sheath ring (Wang et al , 2017). This also means that the first sheath ring can only be connected to the baseplate by six linkers and not by twelve as in the wild‐type assembly or in the T4 phage (Kudryashev et al , 2015; Taylor et al , 2016). Even though our reconstruction lacks the resolution needed to resolve details of sheath–baseplate connection, there is a density originating from a sheath protomer likely corresponding to the VipB C‐terminal linker, which is most likely connected to TssE in the wedge (Fig EV4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional and structural studies have shown that the T6SS nanomachine shares striking similarities with the bacteriophage tail structure (14)(15)(16)(17)(18)(19)(20)(21)(22). Accumulating evidence suggests that the baseplate complex is recruited into the membrane-associated protein complex and initiates the polymerization of a TssB-TssC (VipAVipB) contractile sheath.…”
mentioning
confidence: 99%